Analisis Kinerja Keuangan PT. BANK CENTRAL ASIA Tbk Periode 2014–2018 - Merry Christy; Mas Wibowo Andoko; Duwi Riningsih (CAHAYA AKTIVA, 2021)
This research is expected to be able to find out about the Health Level contained in PT. Bank Central Asia Tbk in the period 2014–2018. Soundness in the Bank is an important aspect that must be known and understood by the bank’s stakeholders. In addition to the function of banks is an institution that aims for financial intermediation, the existence of bank health research can also provide an ease in making a decision in the future that will occur in the future. Used by internal parties as a benchmark of the performance of a bank. In 2011, the Bank’s Soundness was assessed using the RGEC method covering aspects of Risk Profile which included NPL and LDR, Good Corporate Governance ,Earning which included ROA and NIM and Capital with CAR. The method of analyzing a data that will be used is the method of financial analysis that refers to a Otoritas Jasa Keuangan No.4/POJK.03/2016 concerning Rating of Soundness of Commercial Banks. Based on these result, it shows that the Risk Profile aspect which includes NPL and LDR is considered Very Healthy. In the Earning and Capital aspects of the period 2014 – 2018 PT. Bank Central Asia Tbk is considered very healthy. So that PT. Bank Central Asia Tbk is a bank that has the title of very healthy for the pas five years. Keywords: Financial Soundness, Risk Profile, Good Corporate Governance, Earning, Capital.